IMPROVED TECHNOLOGY OF FINISHING WORK WITH EXTEND THE LIFE CYCLE OF URBAN HOUSING (Municipal economy of cities. Series: «Economy science», 2013)
Analyze performance indicators paint facades. The limit economically viable costs to these activities and to combine the problem of aesthetic and economic efficiency in the formation of stains of color facades built environment.